2016
DOI: 10.1155/2016/1752379
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Obstetrics and Gynecology Residents Regarding Pneumococcal Vaccination in Pregnancy: Education, Knowledge, and Barriers to Vaccination

Abstract: Objective. The 23-valent pneumococcal vaccine is recommended for adults over 65 years of age and younger adults with certain medical conditions. The Centers for Disease Control and Prevention (CDC) state insufficient evidence to recommend routine pneumococcal vaccination during pregnancy, but the vaccine is indicated for pregnant women with certain medical conditions. We designed this project to gauge obstetrics and gynecology (OB/GYN) resident knowledge of maternal pneumococcal vaccination. Methods. We admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Moreover, at-risk pregnant individuals should be counseled on the benefits of the pneumococcal vaccine [1]. Among our study cohort, pneumococcal vaccine uptake was low throughout the study period, consistent with prior reports of poor obstetric provider knowledge about the pneumococcal vaccine [20,21]. A 2020 survey assessing resident knowledge on pneumococcal vaccine during pregnancy found that obstetrics and gynecology residents expressed a comfort level of 3.8/10 in regards to understanding potential candidates for the vaccine [20].…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, at-risk pregnant individuals should be counseled on the benefits of the pneumococcal vaccine [1]. Among our study cohort, pneumococcal vaccine uptake was low throughout the study period, consistent with prior reports of poor obstetric provider knowledge about the pneumococcal vaccine [20,21]. A 2020 survey assessing resident knowledge on pneumococcal vaccine during pregnancy found that obstetrics and gynecology residents expressed a comfort level of 3.8/10 in regards to understanding potential candidates for the vaccine [20].…”
Section: Plos Onesupporting
confidence: 87%
“…A 2020 survey assessing resident knowledge on pneumococcal vaccine during pregnancy found that obstetrics and gynecology residents expressed a comfort level of 3.8/10 in regards to understanding potential candidates for the vaccine [20]. Another study on a nationally representative sample of residents found that the majority of residents demonstrated low or moderate knowledge of the indications for pneumococcal vaccine during pregnancy [21]. Areas for future work include examining whether improving provider knowledge of pneumococcal vaccine eligibility criteria results in improved patient receipt of indicated vaccines.…”
Section: Plos Onementioning
confidence: 99%